Access of firms to public procurement in Russia in the 2000s: before and after radical reform of regulation. (13th August 2012) - Yakovlev, Andrei; Demidova, Olga
This paper considers the consequences of public procurement reform in Russia in 2005–2006. We show that before the reform, manufacturing firms with government stakes, old firms and larger firms had advantages in access to government orders. In 2009 large firms retain their advantages in access to government orders. Estimated scales of 'kickback' in 2009 were virtually the same as in 2005. Active restructuring of the enterprises had no infl uence on the enterprises' access to government orders. We discuss the reasons for this failure of the radical reform of public procurement in Russia, and provide some policy implications.